An Analysis of Naomi Wolf's Power Feminism on the protagonist of Sweet Avocadoes' Digital Novel The Alpha's Betrayal in 99 Days on the iReader Platform - Ayu Hudzaifah; Riskia Sitti Velini; Pangeran Muhammad Faqih Syafaat; Irfa Luthfia Rahmani; Nadya Ramadhanty (Universitas Bengkulu, 2026)
Using Naomi Wolf's idea of power feminism, this study uses a descriptive qualitative methodology. The study centers on a female character's quest for domination in the face of men's powerful predominance. The study's focus is Sweet Avocadoes' English-language digital novel The Alpha's Betrayal in 99 Days, which was released on the iReader platform. This reading and writing app distributes over 600,000 titles to over 70 million active readers in more than 150 countries, including Malaysia and Indonesia. The purpose of this study is to reveal the forms and functions of power represented through the main female character, Shayna Anderson. The findings indicate that female power in the novel is portrayed through personal charm, physical strength, resilience, and decisiveness. These attributes enable the protagonist to dominate male characters and negotiate an equal gender position. Thus, the novel emphasizes that women can claim authority in patriarchal social relations through a combination of charisma, strength, and courage. In this study, the author also examines the perspective of women in Islamic teachings as a point of comparison. In addition to challenging the presumption that gender equality is associated with patriarchal culture, this discussion attempts to investigate how the idea is positioned inside the Islamic faith. The writer aims to show that through the teachings of the Qur'an, Islam promotes women's rights and equality with men in several spheres of life, in addition to acknowledging their existence. As a result, this section emphasizes the significance of feminist principles found in Qur'anic texts as a basis for creating a more equitable and proportionate understanding of women's roles in Islam. Keywords: Dominance, Female Equality, Feminism, Power